2015
DOI: 10.1111/famp.12130
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous Loss Experienced by Transnational Mexican Immigrant Families

Abstract: In this study, an ambiguous loss framework as described by Boss (1999, Ambiguous loss: Learning to live with unresolved grief, First Harvard University Press, Cambridge, MA) was used to examine and understand the family experiences of Mexican immigrant agricultural workers in Minnesota. Transcripts from interviews with 17 workers in Minnesota and 17 family members in Mexico were analyzed using qualitative methodology to identify experiences of ambiguous loss in the participants' narratives. Key dimensions of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 36 publications
2
52
1
Order By: Relevance
“…These studies illuminate emotional coping among mothers of migrants; yet, to better understand the gendered nature of transnational parenting, fathers of migrant must also be studied. Building on these and other emergent literature emphasizing the emotional impact of migration (Boccagni and Baldassar ; Solheim, Zaid, and Ballard ), the current study aims to further this research by examining the emotional implications of transnationalism specifically on both mothers and fathers of migrants.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies illuminate emotional coping among mothers of migrants; yet, to better understand the gendered nature of transnational parenting, fathers of migrant must also be studied. Building on these and other emergent literature emphasizing the emotional impact of migration (Boccagni and Baldassar ; Solheim, Zaid, and Ballard ), the current study aims to further this research by examining the emotional implications of transnationalism specifically on both mothers and fathers of migrants.…”
Section: Current Studymentioning
confidence: 99%
“…Many parents had not seen their children in person for many years, and expressed sadness not just over missing them but over the belief that they would never return to live in Mexico. Extended separation and the undocumented context imbues uncertainty and emotional strain that are reflective of the ambiguous loss originally theorized by Boss () and later discussed in the context of migration by Solheim and colleagues (); in effect, parents are torn between accepting a permanent separation from their migrant children and maintaining the hope that they will return. This ambiguity appears to heighten the emotional toll that parents experience, and elicits a unique emotional coping dynamic for the parents of migrants.…”
Section: Implications Of the Undocumented Contextmentioning
confidence: 99%
“…Many of these immigrants remit financial resources to family members who remain in Mexico. Although migrating family members experience stress due to acculturation transitions in their new environments, remaining family members may also experience considerable distress resulting from absence of family members (Graham & Jordan, 2011;Lahaie, Hayes, Piper, & Heymann, 2009;Solheim, Zaid, & Ballard, 2015). This study examines factors that contribute to Mexican family members' psychological distress, especially effects of having family members who migrate to work in the U.S.…”
Section: Family Member's Transnational Migration Community Contextsmentioning
confidence: 99%
“…Due to a gendered pattern in which men typically migrate from Mexico to the U.S., research has focused on wives who remain in Mexico (Boehm, 2008;Radel & Schmook, 2009). Many studies show that changes in family roles and living arrangements combine with feelings of loss to increase psychological distress for remaining spouses (Boehm, 2008;Martone, Muñoz, Lahey, Yoder, & Gurewitz, 2011;Radel & Schmook, 2009;Solheim et al, 2015). One source of this stress is increased responsibility and labor demands for women (Boehm, 2008;Radel & Schmook, 2009), but Nobles et al (2014) found that stress is associated mainly with absence of spouses rather than influenced indirectly by decreased household resources or increased caregiving burdens.…”
Section: Family Contextmentioning
confidence: 99%
“…These methods are, of course, applied within specific treatments in particular ways, but these concepts and methods are also readily exported into the integrative method of the practitioner. And, finally, there is the vast underlying base of knowledge about relational life from which all effective practice draws, including the myriad of empirical findings that we catalog in this journal about family life that is so essential to effective practice [the wide range of such findings includes such diverse information as understanding the impact of partner affairs (Whisman, ), the ways in which resilience occurs (Lietz, Julien‐Chinn, Geiger, & Hayes Piel, ; Walsh, ), the impact of ambiguous loss (Solheim, Zaid, & Ballard, ), the nature of LGBTQ issues in families (Green & Mitchell, ), the impact of various cultural contexts on families (Killoren, Wheeler, Updegraff, Rodríguez de Jésus, & McHale, ; Updegraff & Umaña‐Taylor, ), and relational assessment (Hamilton, Carr, Cahill, Cassells, & Hartnett, ; Heyman, Slep, & Foran, ; Wamboldt, Cordaro, & Clarke, )].…”
mentioning
confidence: 99%